Analisis Komparasi Pendapatan Usahatani Karet Menjadi Kelapa Sawit Di Kecamatan Dolok Sigompulon - Nurjannah Pohan; Supristiwendi Supristiwendi; Thursina Mahyuddin (Jurnal Penelitian Agrisamudra, 2022)
This study aims to analyze the income comparison between rubber farming and rubber farming that has been converted into oil palm in Dolok Sigompulon District, North Padang Lawas Regency. This research was conducted in three villages namely Salusuhan, Sababangun and Panyabungan villages. The sampling method is the Cluster Random Sampling technique. The research sample was 50 consisting of 25 rubber farmers and 25 farmers who had converted to oil palm. Based on the results of the average difference testusing Independent Sample T-Test, it was found that the value. Sig. (2-tailed) 0.002 < 0.05, which means that there is a significant difference between the income of rubber farming and farming that has been converted to oil palm. With total income of rubber farming is Rp. 9,900,051.30/Ha/Year, while the farm income that has converted into oil palm is Rp. 16,938,989.65/Ha/Year.